Front‐to‐back ratio improvement of printed antennas based on electrically small resonators for microwave presence detectors. Issue 11 (1st May 2015) - Aguilà, P.; Zuffanelli, S.; Zamora, G.; Paredes, F.; Martín, F.; Bonache, J.
Abstract : The improvement of the front‐to‐back ratio (FBR) in low‐profile antennas to be used in presence detection devices is explored. The main idea is to use electrically small resonators as radiating elements. This minimises the electric currents in the boundary of the ground plane at the working frequency, thus reducing the backward radiation. The choice of the resonant particle and its electromagnetic properties, along with the antenna structure, are discussed. The simulated results indicate that there is good impedance matching (−18 dB) at the operating frequency (3 GHz) and an excellent FBR of 24 dB. These characteristics are validated experimentally and the FBR is compared with that of a conventional patch antenna.